Dynamic Local Political Elite in Process for Proposing Regional Expansion - Hilal Ramdhani; Valina Singka Subekti (Universitas Pancasakti Tegal, 2020)
Regional expansion though still in the moratorium stage, but political movements carried out by the local political elite are getting stronger at the local level. The dynamics of the local political elite in the process of proposing regional expansion is based on issues in the political elite that support, also reject. In the case of proposing the Cirebon Province, the regional division movement into a Province has been carried out since 2009, precisely when the Presidium for the Establishment of the Cirebon Province was declared, but until 2019 it could not form a solid coalition at the local level. This study uses a qualitative approach with case studies that use interviews, observation and documentation as data collection techniques. The results showed that until 2019 there had not been a solid coalition at the local level, because the issues of ethnicity, regional development, political history and natural resources became a tool used by local political elites to not join coalitions at the local level, these results showed differences with the case in Gorontalo and in Banten, when the political elite joined to fight for the division of the Province on the basis of the same political history.